Converting Access Microbiology to an open research platform: focus group and AI review tool research results. Issue 4 (19th April 2021) - Howat, Alexandra M.; Mulhern, Alexander; Logan, Hilary F.; Redvers-Mutton, Gaynor; Routledge, Chris; Clark, Justin
Abstract : The Microbiology Society will be launching an open research platform in October 2021. Developed using funding from the Wellcome Trust and the Howard Hughes Medical Institute (HHMI), the platform will combine our current sound-science journal, Access Microbiology, with artificial intelligence (AI) review tools and many of the elements of a preprint server. In an effort to improve the rigour, reproducibility and transparency of the academic record, the Access Microbiology platform will host both preprints of articles and their Version of Record (VOR) publications, as well as the reviewer reports, Editor's decision, authors' response to reviewers and the AI review reports. To ensure the platform meets the needs of our community, in February 2020 we conducted focus group meetings with various stakeholders. Using articles previously submitted to Access Microbiology, we undertook testing of a range of potential AI review tools and investigated the technical feasibility and utility of including these tools as part of the platform. In keeping with the open and transparent ethos of the platform, we present here a summary of the focus group feedback and AI review tool testing.